Sealed with a secret - Schroeder, Lisa (New York : Scholastic Press, 2016)
In the beautiful Cartier makeup compact she bought at a flea market, Phoebe finds a letter written during World War II in London, from one sister to another, which contains a "spell" for bringing people closer together, a kind of treasure hunt around London--and Phoebe could really use such a spell, because her older sister, Alice, will be leaving for university soon, and just now she seems to be cutting Phoebe out of her life.
630
Accelerated Reader AR
Keywords: Sisters -- Juvenile fiction; Families -- Juvenile fiction; Antiques -- Juvenile fiction; Magic -- Juvenile fiction; Treasure hunting -- Juvenile fiction; Sisters -- Fiction; Family life -- England -- Fiction; Antiques -- Fiction; Magic -- Fiction; Treasure hunt (Game) -- Fiction; London (England) -- Juvenile fiction; London (England) -- Fiction; England -- Fiction; Young adult fiction